Javanese-Pragmatic Transfer in the English Exclamations by Jang Hansol - Siagian, Sinta Uli (Journal of Literature, Linguistics, & Cultural Studies, 2024)
Someone who can speak a foreign language is likely to do pragmatic transfer. The pragmatic transfer is when a speaker applies the social and cultural norms of his first language when using a second language (Sofwan, 2014; Saleem et al., 2020; Bu, 2022). This research analyzes the phenomenon of Javanese pragmatic transfer in the English exclamation of a YouTuber named Jang Hansol on his channel "Korea Reomit." It aims to identify the types of pragmatic transfer using Kasper's theory (1992) and the function of the exclamation uttered by Jang Hansol using Ameka's theory (2006). This research is a qualitative descriptive study. The results of this study indicated that Jang Hansol had positive and negative pragmatic transfers in expressing exclamations in English. In the finding section, Jang Hansol did positive, pragmatic transfer more often than negative pragmatic transfer, twelve times and six times, respectively. It demonstrated that Javanese had an influence when Jang Hansol spoke English. Furthermore, the two languages have traits in common, and the hearer's awareness of the speaker's history helps them avoid misunderstanding. Apart from that, there are also various functions in the exclamation spoken by Jang Hansol. Of the eleven exclamations, nine exclamations function expressive, and others serve conative and phatic. The prominence of the expressive function in Jang Hansol's utterances is a result of his recent trip to Indonesia. Many new experiences fascinate him. As a result, exclamations having expressive roles are more common in this research.